2014
DOI: 10.1016/j.celrep.2013.12.021
|View full text |Cite
|
Sign up to set email alerts
|

The Histone-H3K4-Specific Demethylase KDM5B Binds to Its Substrate and Product through Distinct PHD Fingers

Abstract: SUMMARY The histone lysine demethylase KDM5B regulates gene transcription and cell differentiation. It contains three PHD fingers, the biological roles of which remain elusive. Here, we show that the first PHD1 finger of KDM5B binds unmodified histone H3, whereas the third PHD3 finger prefers the trimethylated mark, H3K4me3. RNA-seq analysis indicates that KDM5B functions as a transcriptional repressor for a set of genes. Biochemical analysis reveals that KDM5B associates with components of the nucleosome remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
193
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(212 citation statements)
references
References 37 publications
19
193
0
Order By: Relevance
“…Thus, to confirm that IL-12B transcription is influenced by H3K4me3 methylation, we knocked down KDM5B by using siRNA. KDM5B is the enzyme responsible for demethylation of H3K4me3 (Klein et al 2014). We hypothesized that knocking down KDM5B will result in decreased demethylation of H3K4me3 leading to a higher transcription of IL-12B gene.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, to confirm that IL-12B transcription is influenced by H3K4me3 methylation, we knocked down KDM5B by using siRNA. KDM5B is the enzyme responsible for demethylation of H3K4me3 (Klein et al 2014). We hypothesized that knocking down KDM5B will result in decreased demethylation of H3K4me3 leading to a higher transcription of IL-12B gene.…”
Section: Discussionmentioning
confidence: 99%
“…KDM5B is expressed at greater levels in breast cancer cells. H3K4me3 (Klein et al, 2014), while in MCF7 cells, KDM5B knockdown did not alter global H3K4me3 levels but did reduce H3K4me3 at specific genes (Li et al, 2011, Yamane et al, 2007. Over-expression of KDM5B in MDA-MB-231 cells suppressed the metastatic properties of these cells (Klein et al, 2014).…”
Section: H3k4me3 Erasersmentioning
confidence: 94%
“…However, it is an interesting observation that all of the KDM5 family members are associated with HDAC1/2 (Li et al, 2011, Barrett et al, 2007, Tahiliani et al, 2007. KDM5B is associated with the HDAC1/2 NuRD complex (Klein et al, 2014, Li et al, 2011. It is also possible that the KDM5 family members are associated with the HDAC1/2, which is bound to RNA splicing factors (such as SRSF1 and SF3B1-4) .…”
Section: H3k4me3 Erasersmentioning
confidence: 95%
“…In this study, we demonstrated that JARID1B is critical for the recruitment of GATA3 to the Foxa1 promoter and its transcriptional activation. As an H3K4me3/2 demethylase, JARID1B binding at the gene promoters can lead to decreased gene expression (19,39), but its recruitment to the intragenic regions (40) or enhancers (41) was shown to activate gene expression. In mammary epithelial cells, JARID1B loss induced a decrease rather than an increase in H3K4me3 levels at many of its target promoters.…”
Section: Discussionmentioning
confidence: 99%